Cervical spine intramedullary cysticercosis in a young adult - a case report and literature review - Hedaoo, Ketan; Garg, Sunil; Thanvi, Sharad; Agay, Ashuvi Kunjan; Nagocha, Vallabh; Rao, Meenakshi (International Journal of Research in Medical Sciences, 2017)
Neurocysticercosis, is the most common central nervous system parasitic infestation worldwide, but spinal involvement by neurocysticercosis is relatively rare. Here we report a case of 18-year-old male patient with intramedullary cysticercosis caused by Tenia soleum in cervical spinal cord. MRI revealed expansile illdefined intramedullary mass at C4 and C5 vertebral level which believed to be a tumor instead, rather than a cysticercosis preoperatively. surgery was performed to decompress the spinal cord. Histopathological examination of removed lesion confirmed it as cysticercosis.